LYKIA TİYATROLARINA GENEL BAKIŞ. - ÖZDİLEK, BANU (CEDRUS, 2016)
It is stated that theater culture began in the Lycian Region with its early theaters functioning from the Late Archaic-Classical era. The examples demonstrating the traditional form with a cavea in the Lycian region are dated to the Hellenistic era. According to their capacities the Lycian theaters are divided into three: small, medium and large. The initial periods of theaters in the large citifes date from the late Hellenistic and early Roman era. The first theaters had smaller caveas and are listed as medium scale according to their capacities. In the earthquake in 141 A.D. in the Lycian region theatres in cities were damaged and Opramoas from Rhodiapolis provided monetary aid for their reconstruction and repair. The second theatre phase corresponds with the 2nd century A.D. (the Antonine era). In particular the elaborate stage of theaters are believed to have been built in this period. The 3rd building phase corresponds with the IIIrd century A.D., the reign of Septimius Severius, when intense construction activities were undertaken throughout Anatolia. In some theaters both decoration and construction inscriptions dating from this period can be found. After the earthquake of 240 A.D. there was the final phase of construction and repair of importance for Lycian theaters. In the Roman era the capacities of theaters increased. Both the Myra and Limyra theaters were constructed of Roman theater form, with their caveas placed on vaults and arcades. In the Roman era the architecture of theaters changed, with the arenaconverted to serve for animal fights and gladiatorial contests. In the Roman era theaters provided popular entertainment typical of the.main Roman tradition and social life. In this study the general features of Lycian theaters are evaluated forming a summary.